High-level production of d-arabitol by Zygosaccharomyces rouxii from glucose: Metabolic engineering and process optimization. (January 2023) - Li, Xiaolan; Zhang, Yufei; Zabed, Hossain M.; Yun, Junhua; Zhang, Guoyan; Zhao, Mei; Ravikumar, Yuvaraj; Qi, Xianghui
Graphical abstract: Highlights: First report on metabolic engineered non-type yeast for d -arabitol production. Enhancing the innate d -ribulose pathway promoted d -arabitol production. Increasing precursor supply substantially improved d -arabitol synthesis. Cofactors regeneration efficiently increased d -arabitol titer. The highest d -arabitol titer of 149.10 g/L was achieved in non-type Z. rouxii . Abstract: d -Arabitol is a top value-added compound with wide applications in the food, pharmaceutical and biochemical industries. Nevertheless, sustainable biosynthesis of d -arabitol is limited by lack of efficient strains and suitable fermentation process. Herein, metabolic engineering and process optimization were performed in Zygosaccharomyces rouxii to overcoming these limitations. Adopting systems metabolic engineering include enhancement of innate biosynthetic pathway, supply of precursor substrate d -ribulose-5P and cofactors regeneration, a novel recombinant strain ZR-5A with good performance was obtained, which boosted d -arabitol production up to 29.01 g/L, 59.31 % higher than the parent strain. Further with the optimum medium composition and fed-batch fermentation, the strain ZR-5A finally produced 149.10 g/L d -arabitol with the productivity of 1.04 g/L/h, which was the highest titer ever reported by Z.rouxii system. This is the first report on the use of metabolic engineering to construct Z. rouxii chassis for the sustainable production of d -arabitol.